2019
DOI: 10.1002/nav.21872
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pricing and matching in ride‐hailing platforms

Abstract: Ride‐hailing platforms such as Uber, Lyft, and DiDi have achieved explosive growth and reshaped urban transportation. The theory and technologies behind these platforms have become one of the most active research topics in the fields of economics, operations research, computer science, and transportation engineering. In particular, advanced matching and dynamic pricing (DP) algorithms—the two key levers in ride‐hailing—have received tremendous attention from the research community and are continuously being de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(101 citation statements)
references
References 48 publications
0
80
0
Order By: Relevance
“…However, the performance of the optimization algorithm depends heavily on current knowledge. In real cases, time window batch is a common method for processing of matching pool in realtime dispatch [14]. e longer the time window is, the more optimal the solution is, but it is lesser applicable because it will cause longer waiting times for users.…”
Section: Methodsmentioning
confidence: 99%
“…However, the performance of the optimization algorithm depends heavily on current knowledge. In real cases, time window batch is a common method for processing of matching pool in realtime dispatch [14]. e longer the time window is, the more optimal the solution is, but it is lesser applicable because it will cause longer waiting times for users.…”
Section: Methodsmentioning
confidence: 99%
“…Zha et al [48] studied the peak pricing effect on ride-hailing platforms under different assumptions of labor supply behavior. Yan et al [7] used data from Uber to show that, by jointly optimizing the dynamic pricing and dynamic waiting, price variability can be mitigated while increasing the capacity utilization, trip throughput, and welfare. Guda and Subramanian [49] considered the strategic interactions among ride-hailing platform drivers when deciding to move across regions and found that even in areas where driver supply exceeds demand, peak pricing can be profitable.…”
Section: Ride-hailing Platformsmentioning
confidence: 99%
“…e ride-hailing platform's application usually shows that there are more than a dozen people in the queue with an average wait of 20 minutes or that the driver is far away, etc (Xinhua news [6]). To solve these difficulties, some ride-hailing platforms try to dynamically adjust the price to match the supply and demand (Yan et al [7]). For example, DiDi's Spring Festival service fee and the daily price adjustment mechanism for the morning peak are based on supply and demand.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations